Pengaruh tingkat pendidikan dan motivasi wirausaha terhadap penggunaan bootstrap financing - Valina Puby Carolina (Journal of Business & Banking, 2015)
Bootstrap financing is commonly used by entrepreneurs as an alternative to access the capital and manage the business financing. In addition, bootstrap capital provides entrepreneurs with financing alternatives that are confronted by the lack of access the traditional sources of capital. Besides, bootstrap can be used by entrepreneurs that want to manage their business financing by themselves without any intervention from others. Although bootstrap financing is used by many entrepreneurs, the effect of edu-cation and motivation on this factor is not yet disclosed. This research aims to know the effect of entrepreneurs education and motivation on the application of bootstrap financing methods. It took 92 entrepreneurs for the sample which consists of micro and small entrepreneurs in Surabaya and Sidoarjo, taken by distributing questionnaire. It used sampling methods e.g., purposive and convenience sampling. The analysis tech-niques used were One-Way ANOVAs and simple regression analysis. The results show that education has no effect on the application of bootstrap financing methods, while entrepreneurs motivation has a positive and significant effect on the application of bootstrap financing methods.